Society in flux : two centuries of social theory - Dahms, Harry F. (Emerald Publishing Limited, 2021)
The defining feature of modern society is change - it never rests or provides its members or researchers the comfort and certainty of having attained an adequate understanding of its operations, how it functions, or where it is. Society in Flux: Two Centuries of Social Theory traces how tensions between order, process, structure and agency, and modes of analyzing them have evolved over the last two centuries. Understanding that modern society is perpetually in flux, albeit not across the board, but in different regards at different times, and in different locations or regions, this volume delves into three modes of theorizing: critical theory, classical theory, and systems theory - each representing a different level of reflexivity and a particular way of approaching modern societies. The authors discuss globally known theorists such as August Comte, Herbert Spencer, Karl Marx, Emil Lederer, Max Horkheimer, Theodor W. Adorno, and Niklas Luhmann to present perspectives, analyses, and insights that refer to and are relevant in the social world today.
Includes index.
Keywords: Social sciences -- History.; Social Science -- General.; Society & social sciences.; elektronické knihy; electronic books